A STUDY ON THE CHARACTERISTICS OF MR. WILLY WONKA THAT SET UP THE STAGES OF THE GOLDEN TICKET CHILDREN IN ROALD DAHL'S CHARLIE AND CHOCOLATE FACTORY - Bawono Sudewo; Aris Munandar (Universitas Gadjah Mada, 2013)
The goal of this graduating paper is to know how the unconsciousness minds and habits linking to each other. It discusses the mind that triggers characters behavior in the Charlie and Chocolate Factory. The writer focuses on the children who get the golden tickets and the owner of the Chocolate Factory (Mr. Willy Wonka).According to Willbur S Scott with his Psychoanalysis Theory on Fictitious Characters, he stated that we can look further about the pattern which motivates the character to express something. It helps the present writer to analyze deeper, by identifying the showed which were done by the children in Roald Dahl’s Charlie and Chocolate Factory.After carying out the research, it shows that their (the five lucky children and Mr. Willy Wonka) subconscious mind triggers bad action which expelled the children from the chocolate factory and good action which made Charlie the champion.